Media communication strategies in the central public administration - Cantor, Dumitrela Florentina; Rus, Mihaela; Tasențe, Tănase (Technium Social Sciences Journal, 2021)
From year to year, the role of Social Media has become increasingly important. In this context, public institutions in Romania have started to use social networks more and more often, in order to increase the interest of citizens for interaction through social media. Usually, online communication channels do not replace other means of communication, but offer the advantage of the large number of users who are increasingly active in these social networks. Also, public institutions maintain a close relationship with the media, given the fact that it can be a good channel of communication with citizens. Through this communication channel, they build a favorable image and make the activity of public administration transparent, which leads to an improvement in the relationship with citizens. Therefore, the relations of public institutions with the media are materialized through the organization of press conferences, through press releases or interviews with public administration leaders.